Rhythmic auditory stimulation promotes gait recovery in Parkinson's patients: A systematic review and meta-analysis - Ye, Xiaofan; Li, Ling; He, Rong; Jia, Yizhen; Poon, Waisang (Frontiers in Neurology, 2022)
Objective: Using rhythmic auditory stimulation (RAS) to improve gait disturbance in Parkinson's disease (PD) is an available treatment option, yet a consensus on its effectiveness remains controversial. We summarized the effects of RAS on gait, functional activity and quality of life in PD patients through a systematic review and meta-analysis. Methods: PubMed, Embase, Web of Science, Medline, and Cochrane Library databases were initially searched to identify relevant literature up to August 2021. Next, the methodological quality of eligible comparative studies was assessed by the Physiotherapy Evidence Database Scale. The treatment effects to clinical outcome in relation to gait, motor activities, and quality of life were analyzed. Results: A total of 18 studies consisted of 774 subjects were included in this meta-analysis. Comparing with the control group, RAS had significantly increased stride length (p< 0.001), accelerated gait speed (p< 0.001), reduced the occurrence of freezing events during walking (P = 0.009), achieved an improvement in Unified Parkinson’s Disease Rating Scale (UPDRS) Ⅱ (p = 0.030), UPDRS-Ⅲ (p<0.001) and Parkinson’s Disease Quality of Life Questionnaire (PDQL) (p=0.009) scores over an interval of one to twenty-six months.). Conclusion: In this meta-analysis of 18 randomized controlled trials, we have demonstrated that RAS improves the general motor functions (UPDRS-III), particularly in gait, mobility and quality of life in patients with Parkinson’s disease.